2017
DOI: 10.1051/0004-6361/201730881
|View full text |Cite
|
Sign up to set email alerts
|

[C II] emission from L1630 in the Orion B molecular cloud

Abstract: Context-L1630 in the Orion B molecular cloud, which includes the iconic Horsehead Nebula, illuminated by the star system σ Ori, is an example of a photodissociation region (PDR). In PDRs, stellar radiation impinges on the surface of dense material, often a molecular cloud, thereby inducing a complex network of chemical reactions and physical processes.Aims-Observations toward L1630 allow us to study the interplay between stellar radiation and a molecular cloud under relatively benign conditions, that is, inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 49 publications
8
78
0
Order By: Relevance
“…This improves on previous comparisons that used velocity unresolved observations of the 158 µm-[CII] line (Natta et al 1994). The velocity resolution of the 158 µm-[CII] line ob-servations in this study was of ≈ 50 km s −1 , while in the observations of Pabst et al (2019) this is 0.2 km s −1 . Additionally, we use models that describe the level population of carbon atoms including the effect of dielectronic capture (Salgado et al 2017a).…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…This improves on previous comparisons that used velocity unresolved observations of the 158 µm-[CII] line (Natta et al 1994). The velocity resolution of the 158 µm-[CII] line ob-servations in this study was of ≈ 50 km s −1 , while in the observations of Pabst et al (2019) this is 0.2 km s −1 . Additionally, we use models that describe the level population of carbon atoms including the effect of dielectronic capture (Salgado et al 2017a).…”
Section: Introductionsupporting
confidence: 73%
“…Here we compare the latest 158 µm-[CII] line maps of Pabst et al (2019) with the CRRLs observed in absorption. The cube of Pabst et al (2019) presents the 158 µm-[CII] line resolved in velocity and samples a region larger than that studied in CRRLs. With this we were able to perform a direct comparison between the lines over the same regions without making assumptions about their velocity structure.…”
Section: Crrls and Fir [Cii] Linementioning
confidence: 99%
See 3 more Smart Citations